Brassinosteroids mediate moderate soil‐drying to alleviate spikelet degeneration under high temperature during meiosis of rice. (10th October 2022) - Zhang, Weiyang; Huang, Hanghang; Zhou, Yujiao; Zhu, Kuanyu; Wu, Yunfei; Xu, Yunji; Wang, Weilu; Zhang, Hao; Gu, Junfei; Xiong, Fei; Wang, Zhiqin; Liu, Lijun; et al.
Abstract: This study tested the hypothesis that brassinosteroids (BRs) mediate moderate soil‐drying (MD) to alleviate spikelet degeneration under high temperature (HT) stress during meiosis of rice ( Oryza sativa L.). A rice cultivar was pot‐grown and subjected to normal temperature (NT) and HT treatments during meiosis, and two irrigation regimes including well‐watered (WW) and MD were imposed to the plants simultaneously. The MD effectively alleviated the spikelet degeneration and yield loss under HT stress mainly via improving root activity and canopy and panicle traits including higher photosynthetic capacity, tricarboxylic acid cycle activity, and antioxidant capacity than WW. These parameters were regulated by BRs levels in plants. The decrease in BRs levels at HT was due mainly to the enhanced BRs decomposition, and the MD could rescue the BRs deficiency at HT via enhancing BRs biosynthesis and impeding decomposition. The connection between BRs and HT was verified by using rice BRs‐deficient mutants, transgenic rice lines, and chemical regulators. Similar results were obtained in the open‐air field experiment. The results suggest that BRs can mediate the MD to alleviate spikelet degeneration under HT stress during meiosis mainly via enhancing root activity, canopy traits, and young panicle traits of rice. Summary statement: Brassinosteroids can mediate the moderate soil‐drying to alleviate spikelet degeneration under high temperature stress during meiosis mainly via enhancing root activity, canopy photosynthetic capacity, and tricarboxylic acid cycle activity and antioxidant capacity in young panicles of rice ( Oryza sativa L.).